2016
DOI: 10.4172/2329-910x.1000212
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of a Soft Ankle Brace Compared to Tape in Acute Lateral Ankle Ligamentous Sprains

Abstract: Background: Ankle sprains are common injuries, associated with high healthcare and societal costs. After sustaining an acute ankle sprain, ankle taping is the standard treatment in the Netherlands. Ankle braces are sometimes used as an alternative. The aim of the present study was to assess the costs-effectiveness of soft ankle bracing compared to ankle tape treatment in patients with an acute lateral ankle ligamentous sprain (ALALS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…However, only recently it has been demonstrated that in healthy athletes different cleat models aren't related to differences in ankle sprain risk factors (Silva et al, 2017a). Moreover, according to our knowledge, and despite deserving the attention of all sports and health professionals (Boer et al, 2014;Kemler et al, 2016), no study has evaluated the influence of different cleat models in ankle sprain risk factors in athletes with postural control deregulation such as CAI.…”
Section: Introductionmentioning
confidence: 99%
“…However, only recently it has been demonstrated that in healthy athletes different cleat models aren't related to differences in ankle sprain risk factors (Silva et al, 2017a). Moreover, according to our knowledge, and despite deserving the attention of all sports and health professionals (Boer et al, 2014;Kemler et al, 2016), no study has evaluated the influence of different cleat models in ankle sprain risk factors in athletes with postural control deregulation such as CAI.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, acute ankle sprains have a high recurrence rate, which is associated with the development of chronic ankle instability (CAI) (2). The mean total costs of an ankle sprain were estimated at €360.60, resulting from medical consumption, rehabilitation, persistent residual symptoms, and high recurrence rates (4). This relatively high cost of treatment means that cost-effective methods for treatment are required for ensuring healthcare sustainability.…”
Section: Introductionmentioning
confidence: 99%